Exosomes from LPS-Stimulated hDPSCs Activated the Angiogenic Potential of HUVECs In Vitro. (15th April 2021) - Huang, Xiangyu; Qiu, Wei; Pan, Yuhua; Li, Jianjia; Chen, Zhao; Zhang, Kaiying; Luo, Yifei; Wu, Buling; Xu, Wenan
Abstract : Background . Exosomes from human dental pulp stem cells (hDPSCs) were indicated to play a positive role in vascular regeneration processes. But the angiogenic capabilities of exosomes from inflammatory hDPSCs and the underlying mechanism remain unknown. In this study, the inflammatory factor lipopolysaccharide (LPS) was used to stimulate hDPSCs, and exosomes were extracted from these hDPSCs. The proangiogenic potential of exosomes was examined, and the underlying mechanism was studied. Method . Exosomes were isolated from hDPSCs with or without LPS stimulation (N-EXO and LPS-EXO) and cocultured with human umbilical vein endothelial cells (HUVECs). The proangiogenic potential of exosomes was evaluated by endothelial cell proliferation, migration, and tube formation abilities in vitro. To investigate the proangiogenic mechanism of LPS-EXO, microRNA sequencing was performed to explore the microRNA profile of N-EXO and LPS-EXO. Gene Ontology (GO) analysis was used to study the functions of the predicted target genes. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis was used to estimate the signaling pathways associated with the inflammation-induced angiogenesis process. Result . Compared to the uptake of N-EXO, uptake of LPS-EXO activated the angiogenic potential of HUVECs by promoting the proliferation, migration, and tube formation abilities in vitro. The mRNA expression levels of vascular endothelial growth factor (VEGF) and kinase-insert domain-containing receptor (KDR) in the LPS-EXO group were significantly higher than those in the N-EXO group. MicroRNA sequencing showed that 10 microRNAs were significantly changed in LPS-EXO. Pathway analysis showed that the genes targeted by differentially expressed microRNAs were involved in multiple angiogenesis-related pathways. Conclusion . This study revealed that exosomes derived from inflammatory hDPSCs possessed better proangiogenic potential in vitro. This is the first time to explore the role of exosomal microRNA from hDPSCs in inflammation-induced angiogenesis. This finding sheds new light on the effect of inflammation-stimulated hDPSCs on tissue regeneration.